REALISTIC FACTORS THAT LED TO THE CREATION OF TAKHIR MALIK'S FANTASTIC WORKS (World Bulletin of Social Sciences, 2025)
This article discusses the interpretation of realistic ideas embedded in Tahir Malik's fantasy works. This topic is mainly revealed on the example of the story "Hunting." The author's works such as "Falak," "Khizr's Water," "Madman," "Loyalty," "The Dangerous Discovery of X" serve as an auxiliary object of the topic. A distinctive feature of T. Malik's fantasy is that it has never been detached from realism. At the heart of each of his fantasies lies a certain realistic foundation. This can also be seen in the example of the characters that the author introduces into his science fiction work, since in all the author's works, both large and small, which belong to the category of science fiction, at most three or four characters of a science fiction nature participate, while real characters with human qualities number several dozen, and in some cases about fifty. The vitality of the writer's science fiction lies in the fact that in each of his works, he identified a specific social phenomenon, a scientific innovation, natural disasters that occurred on our planet or artificial disasters caused by human damage to nature, the restoration of history prohibited by the Soviets, and even the immortalization of individual names as a real reason, establishing them as the root of the work's idea or the end of the thread, and was able to provide serious reasons that convinced the reader of this fantasy.
Keywords: Realism; fantastic hypothesis; image of a deer